2020
DOI: 10.21009/jobbe.004.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Behind The Positive Attitude of The Indonesian Army Academic Staff: A Rasch Model Analysis

Abstract: The Indonesian National Army is an integral part of the Indonesia Archipelago. As the national component, the Army has the main task of maintaining the country's sovereignty and territorial integrity of the unitary state. Therefore it needs high-quality human resources. The aim of the research was examining the real motivational factors behind the positive attitude of The Indonesian Army Academic Staff. The study applied a Rasch Model method. The Rasch Model Analysis was used to examine the research variable b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These findings are consistent with prior research, which found that personnel in the public sector should be service-oriented rather than profit-driven and actively participating. They should be motivated by the benefits and rewards of their job (Abidin et al 2020;Rafsanjani et al 2019;Valor-Segura et al 2020).…”
Section: Rasch Model Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with prior research, which found that personnel in the public sector should be service-oriented rather than profit-driven and actively participating. They should be motivated by the benefits and rewards of their job (Abidin et al 2020;Rafsanjani et al 2019;Valor-Segura et al 2020).…”
Section: Rasch Model Analysismentioning
confidence: 99%
“…Employees in the public sector should be customer-focused rather than profit-driven and actively involved. They should be motivated by the benefits and rewards of their job (Abidin et al, 2020;Rafsanjani et al, 2019;Valor-Segura et al, 2020).…”
Section: Rasch Model Analysismentioning
confidence: 99%
See 2 more Smart Citations